Navigating borders' multiplicity: the critical potential of assemblage. Issue 2 (7th December 2015) - Sohn, Christophe
Abstract : Various critical and scholarly works have underlined the multiplicity of borders, or the idea that borders mean different things to different people. This paper discusses the potential of the concept of assemblage for better understanding the ontological multidimensionality intrinsic to borders. An assemblage is understood to be a heterogeneous and open‐ended grouping of elements that do not form a coherent whole that helps explain how different meanings emanating from various actors may interact and endure in a contingent and provisional way. It can be argued that such a topological approach may be well suited to highlight the overall significance of a border's identity beyond its diversity and on‐going transformation.